200 años después Los Andes en la encrucijada de las Independencias - Marchena Fernández, Juan; Cuño Bonito, Justo (Biblioteca Historia de América, 2022)
Between the years 2020-2022, various commemorative events of national, regional or local independence have been held, without a meeting that encompasses them. This was the objective of the International Seminar 200 years later. The Andes at the crossroads of the Independences (Seville, December 2021) that we now present in this volume. The purpose of the activity was to analyze and study as a whole the Independence processes in the Andean region and the reciprocal impact of the events in Spain after the Riego uprising in 1820, with the triumph of revolutionary liberalism in Spain and the reestablishment of the Constitution. of Cadiz both in the peninsula and in America. Without forgetting the impact of the liberal revolution in Portugal in 1820, its influence on the independence of Brazil and its repercussion in the Andean region. The Seminar was organized by the Area of ​​American History of the Pablo de Olavide University of Seville, the International University of Andalusia and the La Rábida Group of Ibero-American Universities.